A Poet on the Edge of Generation: Poetic Itinerary of Joan Margarit (Castilla. Estudios de Literatura, 2017)
This article studies both the biographical construction and the poetic itinerary of Joan Margarit. Starting from the literary production of his beginnings, we analyze the decisive influence of his job as an architect in his creative work. Likewise, we observe the importance of writing in two languages for his development and his reception by literary criticism at the national level. This circumstance led to his being known before in the scope of the Catalan language than in the Spanish one, and therefore not included in the collective anthologies of the sixties and seventies, along with the poets born in the same period. This way, Margarit’s poetry has been developed by drawing a personal itinerary, not attached to any group aesthetics, which makes it difficult to frame him in any poetic generation and endows his work with complete uniqueness..
Keywords: Joan Margarit; poetry; literary education; poets in Spanis language; poets in Catalan language